Pembangunan Pembangunan Irigasi Di Afdeeling Demak dan Grobogan Masa Awal Abad XX: Sebuah Kajian Historis - Endah Sri Hartatik (Diakronika, 2022)
Abstract Although the Demak and Grobogan regions are food buffer areas in Indonesia, especially rice, during the Dutch colonial period, they were food insecure areas. This study aims to reveal the history of irrigation policy in the region. The method used is a historical method emphasizing the use of Semarang Residency archive sources. Demak and Grobogan during the colonial period were known as areas prone to famine. The Dutch colonial government and the local government tried to overcome this hunger by building infrastructure to support rice production. Irrigation development was the main policy developed by the Colonial Government from the end of the nineteenth century to the beginning of the twentieth century. As a result of the construction of irrigation facilities, rice production increased so as to reduce the level of hunger and poverty of the people of Demak and Grobogan at that time. Keywords: Colonial, local, irrigation, hunger, production